Gestión administrativa y la innovación tecnológica en empresas del sector plástico - Montenegro Delgado, Marjorie Teresa (2023)
The purpose of this research work Administrative Management and technological innovation in companies in the plastic sector is to analyze the importance of administrative management and technological innovation in the filing process, evidencing that the physical file is not the most appropriate, demonstrating that the change to a digital storage model is a priority. The sample is chosen at the convenience of the researcher, the selected company is Plastimagic S.A. whose corporate purpose is the manufacture and marketing of plastic construction products, who indirectly provides information, providing facilities to the researcher. In the first chapter General Framework, the relevance of the Theme, the contribution to the company, the argument and the importance of this research are emphasized. In the second chapter is the Theoretical Framework, it is taken as a conceptual basis of theories related to Administrative Management, Phases, Plastic Sector Company, Technological Innovation. The Legal Framework addresses the Ecuadorian legislation associated with the investigation...........